GLYCATED HEMOGLOBIN AS A BIOMARKER TO PREDICT DYSLIPIDEMIA IN TYPE 2 DIABETES MELLITUS - Tariq, Abdul Moueed; Khattak, Abdul Latif; Rehman, Hafiz Yasir; Mehmood, Faisal; Akhtar, Raheel; Ali, Ejaz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To establish the correlation between glycated hemoglobin (HbA1c) and lipid profile in patients with type 2 diabetes mellitus (T2DM).Study Design: Correlation study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi (PEMH), Medical Outpatient department (OPD), from Nov 2017 to May 2018.Methodology: A total of 160 patients with type 2 diabetes mellitus of both genders, 30-70 years of age presenting in OPD were included in study, while those with T1DM, CKD stage 3 and above, infection or diabetic foot, any endocrine disease and female patients with pregnancy were excluded from the study. The blood samples were taken for blood sugar random (BSR), blood sugar fasting (BSF), haemoglobin A1c (HbA1c), lipid profile and results were collected next day. The Pearson correlation test was used to analyze correlations.Results: Among 160 patients the mean age was 57.28 ± 10.13 years, 81 (50.6%) were males while 79 (49.4%) were females. The 34 (21.20%) patients had good, while 125 (78.80%) had poor glycaemic control using haemoglobin A1c of 7% as a cut off. A positive and statistically significant correlation was observed between haemoglobin A1c and total cholesterol (r=0.233, p